Conserved Region CR2 of Epstein-Barr Virus Nuclear Antigen Leader Protein Is a Multifunctional Domain That Mediates Self-Association as well as Nuclear Localization and Nuclear Matrix Association - Tanaka, Michiko (American Society for Microbiology, 2002)
Self-association of viral proteins is important for many of their functions, including enzymatic, transcriptional, and transformational activities. Epstein-Barr virus (EBV) nuclear antigen leader protein (EBNA-LP) contains various numbers of W1W2 repeats and a unique carboxyl-terminal Y1Y2 domain. It was reported that EBNA-LP associates with a variety of cellular proteins and plays a critical role in EBV-induced transformation. We report here that EBNA-LP self-associates in vivo and the domain responsible for the homotypic association is a multifunctional domain mediating nuclear localization, nuclear matrix association, and EBNA-2-dependent coactivator function of the protein. Our conclusions are based on the following observations. (i) EBNA-LP interacts with itself or its derivatives in the yeast two-hybrid system. (ii) A purified chimeric protein consisting of glutathione S-transferase fused to EBNA-LP specifically formed complexes with EBNA-LP transiently expressed in COS-7 cells. (iii) When Flag epitope-tagged EBNA-LP with either one or two W1W2 repeats and EBNA-LP containing four W1W2 repeats were coexpressed in COS-7 cells, the latter was specifically coimmunoprecipitated with the former. (iv) Mutational analyses of EBNA-LP with deletion mutants revealed that the region between codons 19 and 39 (relative to the first amino acid residue of the W2 domain) is essential for self-association of the protein. The mapped region almost completely overlaps with CR2 and CR3, regions conserved among a subset of primate γ-herpesviruses and critical for EBNA-2-dependent coactivator function. Amino acid substitutions in CR2 alone abolished the ability of the protein to self-interact. This laboratory previously reported that CR2 is also responsible for nuclear localization and nuclear matrix association (A. Yokoyama, Y. Kawaguchi, I. Kitabayashi, M. Ohki, and K. Hirai, Virology 279:401–413, 2001). (v) Sucrose gradient sedimentation showed that amino acid substitutions in CR2 reduced the ability of the protein to form protein complexes in B cells. These results suggest that self-association of EBNA-LP may be important for its various functions and interactions of the protein with multiple cellular proteins.